Expert consensus on fertility preservation in hematopoietic stem cell transplantation in girls in China - X. Ruan (Gynecological Endocrinology, 2023)
Aims: Preconditioning before hematopoietic stem cell transplantation (HSCT) seriously damages the ovarian function and causes female infertility. This consensus focuses on the fertility preservation(FP) for girls needing HSCT, aim to make doctors in different disciplines aware of the importance, necessity and technique of ovarian protection.Materials and methods: Summarizing relevant literature and organizing multidisciplinary experts, including obstetrics and gynecology, reproductive medicine, oncology, pediatrics and hematology for full discussion.Results: Individuals exposed to HSCT in childhood are at higher risk of loss of fertility. Considering the high risk of premature ovarian insufficiency (POI) after conditioning and negative impact of POI on fertility, physical and mental health, it is absolutely necessary to protect fertility before HSCT conditioning. Ovarian tissue cryopreservation is the main fertility preservation option for these population.Conclusions: Fertility preservation before HSCT conditioning is crucial. Ovarian tissue cryopreservation is often the only option for these population.